2017
DOI: 10.1002/cbin.10828
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐376a suppresses the proliferation and invasion of non‐small‐cell lung cancer by targeting c‐Myc

Abstract: It has been reported that miR-376a is involved in the formation and progression of several types of cancer. However, the expression and function of miR-376a is still unknown in non-small cell lung carcinomas (NSCLC). In this study, the expression of miR-376a in NSCLC tissues and cell lines were examined by real-time PCR, the effects of miR-376a on cell proliferation, apoptosis and invasion were evaluated in vitro. Luciferase reporter assay was performed to identify the targets of miR-376a. The results showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 15 publications
(22 reference statements)
0
26
0
Order By: Relevance
“…Formosa et al (18) demonstrated that the resumption of miR-376a expression attenuates the growth of prostate cancer cells while inducing apoptosis. Wang et al (19) indicated that miR-376a re-expression restricts cell proliferation and invasion while promoting apoptosis in non-small-cell lung cancer. Conversely, miR-376a serves oncogenic roles in ovarian cancer by promoting cell proliferation and motility, inhibiting cell apoptosis in vitro and increasing tumor growth in vivo (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Formosa et al (18) demonstrated that the resumption of miR-376a expression attenuates the growth of prostate cancer cells while inducing apoptosis. Wang et al (19) indicated that miR-376a re-expression restricts cell proliferation and invasion while promoting apoptosis in non-small-cell lung cancer. Conversely, miR-376a serves oncogenic roles in ovarian cancer by promoting cell proliferation and motility, inhibiting cell apoptosis in vitro and increasing tumor growth in vivo (29).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the expression and roles of miRs in OS must be further investigated to identify potential therapeutic targets for the therapy of patients with OS. miR-376a-3p (miR-376a) is dysregulated in several human cancer types and the dysregulation of miR-376a serves an important role in various cell processes, including cell proliferation, migration, invasion, metastasis and apoptosis (16)(17)(18)(19). However, to the best of our knowledge, the expression pattern, clinical significance, specific role and detailed mechanisms of miR-376a in OS remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The 5′terminal seed sequences of mature miRNAs regulate target gene expression at the post-transcriptional level by binding to the 3′-UTR of the target mRNAs, which results in their degradation or translational suppression [29,33]. The biological role of miRNAs has gained considerable attention in recent years, and several have been identified as oncogenes or tumor suppressor genes that regulate proliferation, differentiation, apoptosis and migration of cancer cells [34,35]. Therefore, miRNAs are potential markers for the diagnosis, prognosis, classification, staging and therapeutic monitoring of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from their roles as tumor promoters, some miRNAs function as tumor suppressors by targeting oncogenes. In NSCLC tissues and cell lines, miR-376a was significantly downregulated; the overexpression of miR-376a could inhibit cell proliferation and inva-sion and alsp increase cell apoptosis by decreasing the mRNA and protein levels of c-Myc [23] . MiRNA-183 has been considered a tumor suppressor, which can inhibit the proliferation, migration and invasion of NSCLC cells by targeting MTA1 [24] .…”
Section: Mirnas As Tumor-suppressor Genes In Nsclcmentioning
confidence: 97%